(untitled) (American Journal of Islam and Society, 2017)
“Civilization,” which plays a significant role in today’s world, is a term that has been discussed and debated through the ages and remains so today. In the broader context, and at different levels and contexts (e.g., historical, cultural, and political), it is used to describe “the entirety of collective 90 human values”; “consequential behavior against barbarism” (or simply “the idea of being civilized”); as a “vision of existence and order”; and, above all, as “being an abstraction of modernity and secularism.” One of the most oft-debated concepts in the social sciences, it has largely been framed by Western assumptions and concerns; although there are non-Western perspectives on it as well. A recent addition to the multi-faceted debate on civilization and modernization vis-à-vis the Muslim world is editor Lutfi Sunar’s Debates on Civilization in the Muslim World. Sunar is a Turkish sociologist who teaches at Istanbul University. This collective endeavor of (predominantly young) Muslim scholars seeks to evaluate Muslim views on civilization by challenging the “embedded prejudices within the social theory” and offering “alternative viewpoints” (p. vii). It presents “a complex assessment of key ideas in the modernist discourse from non-ethnocentric perspectives and offers a new understanding of civilization” (p. viii). To achieve this objective, the book has been divided into three main parts. Part 1, “Defining and Discussing Civilization,” consists of three chapters, by Anthony Pagden, Lutfi Sunar, and Mustafa Demirici, respectively, that review, analyze, and discuss definitions of civilization and modernity and their “Eurocentric” understandings. Part 2, “Debates on the Civilization in the Contemporary Muslim World,” examines non-Western civilizations, efforts to resist against being assimilated in Western perspectives and dominance. These chapters are contributed by Vahdettin Isik, Cemil Aydin, Necmettin Dogan, Halil Ibrahim Yenigun, Seyed Javad Miri, Mahmud Hakki Akin, and Driss Habti, respectively. Part 3, “Modernization, Globalization, and the Future of Civilization Debate,” features chapters by Syed Farid Alatas, Yunus Kaya, Murat Cemrek, and Khosrow Bagheri Noaparast, respectively. The volume’s overall theme is designed “to expose complex issues for further discussion pertaining to modernization, globalization, (de)colonization, and multiculturalism” (p. vii). As it is difficult to focus on all the chapters, I provide a brief assessment of some selected ones below ...